Implementasi Sistem Informasi Monitoring Laboratorium Komputer Berbasis Web Menggunakan Metode Waterfall - Willyansah, Willyansah; Ayu, Fitri; Muhammad, Muhammad (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
Monitoring is an activity carried out to monitor, supervise, and observe certain things in a place. Institut Teknologi dan Bisnis Riau has two laboratories, namely software and robotics laboratories, each of which has 30 computers. There is 1 officer who supervises and performs maintenance for the two laboratories. However, of the many computers, routine checks must be carried out so that the learning process always runs well and smoothly. With a minimal number of officers, the learning process will be disrupted if there is damage to one of the computers in the laboratory. For this reason, a laboratory monitoring information system is needed that is useful later in providing reports on the state of computer damage by computer users which here are Institut Teknologi dan Bisnis Riau campus students. The method used is waterfall, this method is suitable for the problem of applying for marriage and reconciliation more easily and quickly. After the system is implemented, the result that will be obtained is an integrated system that becomes easier. The results of testing this information system will later display reports from students regarding the state of the computer, both related to software and hardware itself.